Correction of Multiple Canine Impactions by Mixed Straightwire and Cantilever Mechanics: A Case Report - Sergio Paduano; Iacopo Cioffi; Giorgio Iodice; Vincenzo d’Antò; Francesco Riccitiello; Gioacchino Pellegrino; Rosa Valletta (Case Reports in Dentistry, 2014)
Background. This case report describes the orthodontic treatment of a woman, aged 17 years, with a permanent dentition, brachyfacial typology, Angle Class I, with full impaction of two canines (13,33), and a severe ectopy of the maxillary left canine. Her main compliant was the position of the ectopic teeth. Methods. Straightwire fixed appliances, together with cantilever mechanics, were used to correct the impaired occlusion and to obtain an ideal torque control. Results and Conclusion. The treatment objectives were achieved in 26 months of treatment. The impactions were fully corrected with an optimal torque. The cantilever mechanics succeeded in obtaining tooth repositioning in a short lapse of time. After treatment, the dental alignment was stable.